(untitled) (Scientific journal of the Fergana State University, 2024)
Such areas of modern world linguistics as linguoculturology, ethnoculturology, linguopragmatics, cognitive linguistics, psycholinguistics, sociolinguistics are based on the principles of the anthropocentric paradigm, according to which the main criterion is the human factor. Issues such as the relationship between language and society, as well as a wide range of national cultural units reflected in it, linguistic cultures, the processes of their formation and scope of application, their manifestation at the language level, manifestation in oral and written speech. The purpose of the study is to determine the national-cultural, lexical-semantic, stylistic features of linguistic cultures in English works of art, as well as to highlight issues of their translation into the Uzbek language.